Comparison of the Genetic Structure betweenIn Situ and Ex Situ Populations of DongxiangWild Rice (Oryza rufipogon Griff.). Issue 6 (23rd August 2017) - Liu, Sha; Zheng, Xiaoming; Yu, Liqin; Feng, Li; Wang, Junrui; Gong, Tingting; Liang, Xinxia; Qi, Lan; Su, Long; Ding, Yingbin; Xu, Rui; Qiao, Weihua; et al.
Abstract : In situ and ex situ conservation are two main wild rice ( Oryza rufipogon Griff.) protection strategies. Few studies have compared the genetic diversity and genetic structure of wild rice between ex situ and in situ populations. Thus in this study, 278 individuals collected from three in situ and nine ex situ populations of Dongxiang wild rice (DXWR) were genotyped using 32 microsatellite loci to compare their population genetic structure and genetic diversity. Model‐based grouping, neighbor‐joining tree, and principal coordinate analyses showed that there were significant differences in the population structure between in situ and ex situ populations. The in situ populations clustered into three major groups, which were in accordance with their geographical distribution (Anjiashan, Zhangtang, and Shuitaoshu). However, the nine ex situ populations of DXWR showed no differences among populations, and there was a high heterozygosity for each individual. In addition, one of the in situ populations (Zhangtang) was not represented in the ex situ conservation garden. Given the above results, we concluded that the germplasm of both in situ and ex situ populations are precious, and that the combination of these two conservation strategies is necessary to protect the germplasm resources of DXWR, but special emphasis should be placed on in situ conservation to better maintain their genetic identities. In addition, it is necessary to recollect genetic resources from in situ populations for ex situ conservation, especially from the Zhangtang population.